Testicular teratoma with nephroblastoma in an adult – case report and literature review - Landin, Caroline; Karlsson, Fredrik M. T.; Småland, Mari Lorier; Gabrych, Anna; Kunc, Michał (Contemporary Oncology/Współczesna Onkologia, 2023)
Testicular germ cell tumours are the most common malignancies in young men. Germ cell tumours can be classified as seminomas or non-seminomas, each with different clinical features and treatment approaches. Germ cell tumours are occasionally associated with somatic-type malignancy, particularly in metastatic lymph nodes after adjuvant chemotherapy. Adenocarcinomas and rhabdomyosarcoma are the most common malignancies in this setting. In this report, we present a unique case of a 37-year-old patient who presented with a testicular teratoma containing a nephroblastoma component. The tumour exhibited characteristic morphology that resembled foetal kidney and expressed nuclear WT-1 and PAX-8 on immunohistochemistry. Following surgery, the patient opted for active surveillance and remains disease-free. To date, only 7 cases of nephroblastoma in primary testicular teratoma have been reported. This case highlights the importance of considering this rare entity in the differential diagnosis of testicular teratomas and the need for careful pathological examination.